Mitas ir metamorfozė Alfonso Nykos-Niliūno poezijoje - Meržvinskaitė, Birutė (Literatūra, 2011)
Straipsnyje analizuojami du mito funkcionavimo aspektai Alfonso Nykos-Niliūno poezijoje. Mitas suprantamas kaip simbolinė fabula ir kaip refleksijos bei interpretacijos objektas, implikuojantis skirtingus pasakojimus apie esmines žmogaus ir kūrybos patirtis. Metamorfozė siejama su pavidalų kaita, pasireiškiančia gamtos ir kultūros pasauliuose.MYTH AND METAMORPHOS IS IN THE POETRY OF ALFONSAS NYKA-NILIŪNASBirutė MeržvinskaitėSummaryThe article discusses two aspects of myth functions in A. Nyka-Niliūnas poetry: 1) myth as symbolic plot that implies different versions of stories about essential human experiences (life and death, nature and culture, face and mask, writing and voice); 2) myth as a field of reflection and interpretation. The reception of the myth relies on the universal principle of return and repetition where cosmological dimension is accompanied by the perspective of the perceiving and enunciating subject. The phenomenon of metamorphosis is manifested as a law of nature, on the other hand, it is related to the transposition of mythical stories and images and their transformations. The article investigates how a law of nature becomes the problem of being and creation in the poetry of A. Nyka-Niliūnas.